The effect of seed reproduction on rice yield structure - P. I. Kostylev; Yu. P. Teslya; E. S. Balyukova (Зерновое хозяйство России, 2020)
Rice in the conditions of the Rostov region is an important food crop. The reproduction process of rice varieties results in its gradual deterioration because of mechanical, biological clogging, spontaneous pollination with impurities, followed by hybrid splitting, as well as an increase in the level of disease damage. Therefore, there is a constant need to update seeds of the cultivated rice varieties. The purpose of the study is to identify the dynamics of rice seed productivity change and elements of yield structure during their reproduction. In laboratory conditions, according to the standard methods there were determined “plant height”, “number and weight of stems and panicles per 1 m2, “length of panicle”, “number of full and empty spikelets on panicles”, and “1000 seed weight”. For the study there were taken the original seeds of the nursery for progeny testing (PIP), reproduction nursery (OS-1), superelite (OS-2) and elite (ES), the varieties “Akustik”, “Boyarin”, “Kuboyar” and “Yuzhanin” grown in the Proletarsky district of the Rostov Region in 2018–2019. It has been established that productivity tends to decrease from higher reproductions (reproduction nursery) to lower ones (elite seeds). The largest seed yield was obtained in the nursery for progeny testing, it was 9.2 t/ha on average for 4 varieties, exceeding the value of elite seeds on 3.2 t/ha.